2017
DOI: 10.1080/20008198.2017.1341276
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian network analysis of posttraumatic stress disorder symptoms in adults reporting childhood sexual abuse

Abstract: Background: The network approach to mental disorders offers a novel framework for conceptualizing posttraumatic stress disorder (PTSD) as a causal system of interacting symptoms. Objective: In this study, we extended this work by estimating the structure of relations among PTSD symptoms in adults reporting personal histories of childhood sexual abuse (CSA; N = 179).   Method: We employed two complementary methods. First, using the graphical LASSO, we computed a sparse, regularized partial correlation network r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(226 citation statements)
references
References 45 publications
7
218
1
Order By: Relevance
“…Across studies, results disclosed strong associations among avoidance symptoms [28, 29] and between hypervigilance and startle response [28, 30-33]. Particularly, McNally et al [34] found that physiological responses to reminders of trauma predicted symptoms such as “being upset” “flashbacks,” and “traumatic dreams,” in a sample of adults who reported histories of childhood sexual abuse. According to these authors, physiological reactivity, which is associated in NA with being female [32], may play a potential causal role in the activation of the PTSD network.…”
Section: Resultsmentioning
confidence: 99%
“…Across studies, results disclosed strong associations among avoidance symptoms [28, 29] and between hypervigilance and startle response [28, 30-33]. Particularly, McNally et al [34] found that physiological responses to reminders of trauma predicted symptoms such as “being upset” “flashbacks,” and “traumatic dreams,” in a sample of adults who reported histories of childhood sexual abuse. According to these authors, physiological reactivity, which is associated in NA with being female [32], may play a potential causal role in the activation of the PTSD network.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in a sample of 179 US adult survivors of childhood sexual abuse, McNally, Heeren, and Robinaugh (2017) in ‘A Bayesian network analysis of posttraumatic stress disorder symptoms in adults reporting childhood sexual abuse’ extend the existing PTSD network analysis research by applying two distinct network models. Firstly, the authors computed an undirected regularized partial correlation network (based on the DSM-IV PTSD symptoms).…”
Section: In This Issuementioning
confidence: 99%
“…These network models estimate conditional dependence relations among items: what is the association between A and B after partialling out the influence of C? In such undirected networks, suggest McNally et al (2017), the causal relationships between symptoms cannot be inferred. Thus, in the second step, the authors utilized a Bayesian approach to computing a directed acyclic network, which leads to a directed network structure often referred to as a ‘causal skeleton’.…”
Section: In This Issuementioning
confidence: 99%
“…neurobiological research, like the oxytocin paper by Frijling (2017), the methodological ones, e.g. McNally, Heeren, and Robinaugh (2017)’s paper on Bayesian statistics, and public health (e.g. Magruder et al, 2017).…”
Section: Estss Ejpt Best Paper Of 2017 Awardmentioning
confidence: 99%